2017
DOI: 10.1542/hpeds.2016-0185
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Chronic Critical Illness: Reducing Excess Hospitalizations

Abstract: Despite an expanding pediatric population with CCI, we lack an intentional care model to minimize their hospitalizations. In this study, we generate several hypotheses for exploring the potential impact of expanded access to home nursing, robust care coordination, and family and clinician support to reduce hospital days for this population of high health care utilizers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Data from both clinicians and families suggest that the "poor fit" of the acute care hospital model for infants with CCI is itself partly responsible for their excess hospital days. 18 Yet the number of these infants and children with CCI is likely to remain high, suggesting the need for adaptations to inpatient care models and clinician training. 19 We have shown that ICU clinicians across the United States feel unprepared to manage chronic patients, citing gaps in clinical training and ancillary supports like case management.…”
Section: Discussionmentioning
confidence: 99%
“…Data from both clinicians and families suggest that the "poor fit" of the acute care hospital model for infants with CCI is itself partly responsible for their excess hospital days. 18 Yet the number of these infants and children with CCI is likely to remain high, suggesting the need for adaptations to inpatient care models and clinician training. 19 We have shown that ICU clinicians across the United States feel unprepared to manage chronic patients, citing gaps in clinical training and ancillary supports like case management.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of interest, such as LOS or cost, vary based on local access to non-ICU care sites (e.g., pediatric long-term care hospitals) and reimbursement structures (e.g., Maryland's Global Budget Revenue). 27 Additionally, as the studies in this review demonstrate, more refined methodologies are needed to account for the many patient, family, clinician, and hospital factors that shape chronic ICU management.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support those of colleagues who noted that these deficiencies in PHHC quality and availability contributed to caregiver burden 20 and excess hospital days. 7,8 Pediatricians or care coordinators should ask how likely the designated PHHC agency is to staff the approved hours. They should also inquire about staffing continuity to help families anticipate filling in gaps or inquire about training new staff.…”
Section: Figurementioning
confidence: 99%
“…6 Without adequate PHHC to help families support their children at home, these children are vulnerable to spending excess days in the hospital. 7,8 Current guidelines suggest that the pediatrician is a fundamental member of the PHHC team, facilitating a coordinated plan of home care. 4,9 Although outpatient pediatrician knowledge of PHHC has not been described in the literature, data suggest that inpatient clinicians may not fully understand the resources needed for CMC at home.…”
mentioning
confidence: 99%